PENGARUH PEMANFAATAN MEDIA LAGU BUGIS TERHADAP KEMAMPUAN MENULIS CERPEN SISWA KELAS XI SMA - Peggi Melati Rudini; Sultan Sultan; Andi Agussalim AJ (Universitas Negeri Makassar, 2020)
The Effect of Bugis Song Media Utilization on the Short Story Writing Ability of Class XI SMA. This study aims to describe the results of learning to write short stories for class XI students of SMA Negeri 2 Pinrang before and after using Bugis song media, and to prove the effect of using Bugis song media on the ability to write short stories of class XI students of SMA Negeri 2 Pinrang. This type of research is pre-experimental, with the One Group pretest-posttest research design. The data analysis technique used is descriptive statistics and inferential statistics. The results showed that the students 'ability to write short stories before using Bugis song media was categorized as quite capable, after using Bugis song media was categorized as quite capable, and the use of Bugis song media had an effect on the students' ability to write short stories.